HUBUNGAN ANTARA REGULASI DIRI DENGAN PENYESUAIAN DIRI PADA SISWA SMK - Maslahatun Nisai; Lailatuzzahro Al-Akhda Aulia (Academic Journal of Psychology and Counseling, 2021)
The ability to adapt is necessary to live well in a social environment. Likewise with students in their teens. The purpose of this study was to determine whether or not there is a correlate of self-regulation with self-adjustment in adolescents. The sample used was 80 students who were taken using cluster random sampling technique. Data collection uses a self-adjustment scale which was developed based on the Schneiders’s theory (1964) and a self-regulation scale which was developed based on the Schunk & Zimmerman’s theory (1998). The data obtained were then analyzed using Product Moment and Regression Analysis. From the results of data analysis shows the value of Sig. is 0,000 (p < 0,05). These results indicate that self-regulation has a correlate with self-adjustment in adolescents. It means, adolescents who have good self-regulation will have good self-adjustment, so they are expected to be able to participate in activities at school without obstacles.